PENINGKATAN PENJUALAN MAIN COURSE MENU PADA PREGO RESTAURANT THE WESTIN RESORT NUSA DUA – BALI (PENDEKATAN MENU ENGINEERING) - KADEK MARTINADEVIE KUSUMA WARDANI; COKORDA GEDE PUTRA YUDISTIRA; NI KETUT SUCIANI; KASIANI KASIANI (Universitas Mahasaraswati K. Mataram, 2023)
Along with the development of the number of tourist visits, also grows various stars hotels in Bali which causes room revenue is no longer the only large income for the hotel so that there is a need for additional sources of income for the hotel, which is restaurants. This research aims to determine the menu mix and contribution margin, and to find out the menu classification also the efforts made to increase sales volume. This research used analysis method with menu engineering approach. This analysis approach used to assess the popularity and profit of a menu item. The results of this research show 32% of the menu included in the “stars” category, 36% of the menu included in the “plowhorses” category, 4% of the menu included in the “puzzles” category, and 28% of the menu included in the “dogs” category. So, the efforts that should be made such as: maintaining the quality, reducing the portion of the menu, menu placement, up to the menu name change.